L’enseignement et la jeunesse vus par l’intelligentsia marocaine - Bernard Schlemmer (Cahiers de la Recherche sur l'Education et les Savoirs)
Has education and youth aperception changed in Morocco ? The answer is given by the Lamalif review (1966-88), a representative review of Moroccan intellectuals. We shall read the review through the looking glass and try to catch any scotomized item : when the author seems to speak of youth, he is only interested with those who will be later intellectuals, when he seems to speak of learning he is mostly interested in the system of education, when he seems to speak on the system of education, he analyzes essentially the system of higher education. But one can notice a certain change : the scotomized items are mainly noticed in the Weltanschaung in the first years ; they show an ideological cleavage and a claim for overthrowing the political system. With the fin de siècle, one can see the emergence of a pragmatic type of reform, not to say a corporate type of reform, which deals better notwithstanding, with the complexity of the social reality. The question of education is still on the move, with the same alacrity and the same motto of crisis, and the same sense of helplessness.